Corporate Duty of Vigilance in Europe: Towards a Semblance of Unity - Aurelie Dardenne (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law, 2024)
Since the 1970s, the idea has emerged that the protection of human rights and the environment should not be the sole responsibility of States. Private actors, and in particular companies, also have a role to play. Despite a number of setbacks on the international stage, corporate due diligence has gradually gained ground. This is particularly true in Europe. Faced with the diversity of responses proposed by Member States, on June 1, 2023, the European Parliament voted in a directive on corporate due diligence with regard to sustainability. A Europe-wide unification of the subject thus seems to be underway.